Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $X_t$ be a generalized Wiener process with drift rate $\mu$ and variance $\sigma^2$, and let $\tau$ be the stopping time

$$\tau:=\inf \left\{ t\geq0: X_t= b\right\}, \quad b\geq0 $$

Can anyone give me some insights on how to compute the generating function:

$$ E[\mathrm{e}^{-\lambda\tau}], \quad \lambda\geq0 $$

Many thanks in advance.

share|improve this question

2 Answers 2

up vote 2 down vote accepted

Here's a solution, perhaps not in the most formal language (i.e. I may be skipping some technical details), and hopefully without any major errors.

If $\tau_b$ is the time until $X_t=b\ge0$ is reached, let us define $$F_\lambda(b)=\text{E}\left[e^{-\lambda\tau_b}\right]$$ for $\lambda>0$, with the convention that $e^{-\lambda\tau_b}=0$ if $X_t=b$ is never reached.

First, we note that $F_\lambda(0)=1$, and that $F_\lambda(b)$ is decreasing in $b$.

If $b>0$, $X_T=x$ and $X_s<b$ for $s<T$, we can let $\hat{X}_s=X_{T+s}-x$ with corresponding $\hat\tau_b=\tau_{x+b}-T$, which makes $$ \text{E}_T\left[e^{-\lambda\tau_b}\middle|X_T=x\right] =\text{E}\left[e^{-\lambda(\hat\tau_{b-x}+T)}\right] =e^{-\lambda T}\cdot\text{E}\left[e^{-\lambda\hat\tau_{b-x}}\right] =e^{-\lambda T}\cdot F_\lambda(b-x). $$ However, if we let $T=dt$, and compute to the first order in $dt$, we get $$ \begin{split} F_\lambda(b) =&\text{E}\left[\text{E}_{dt}\left[e^{-\lambda\tau_b}\middle|X_{dt}\right]\right] =\text{E}\left[e^{-\lambda\,dt}\cdot F_\lambda(b-X_{dt})\right] \\ =&F_\lambda(b)+dt\cdot\left\{-\lambda F_\lambda(b) -F_\lambda'(b)\,\text{E}[X_{dt}] +\tfrac{1}{2}F_\lambda''(b)\,\text{E}[X_{dt}^2] \right\} \\ =&F_\lambda(b)+dt\cdot\left\{-\lambda F_\lambda(b) -\mu F_\lambda'(b)+\tfrac{1}{2}\sigma^2 F_\lambda''(b) \right\} \end{split} $$ which provides us with the differential equation $$ \lambda F_\lambda(b)+\mu F_\lambda'(b)-\tfrac{1}{2}\sigma^2 F_\lambda''(b)=0. $$ We can express the solutions of this as $\alpha_1e^{-\beta_1b}+\alpha_2e^{-\beta_2b}$ where $\beta_i$ are the roots of $\lambda-\mu\beta-\sigma^2\beta^2/2=0$. The equation has one negative and one positive root, and since $F_\lambda(b)$ is declining (towards zero) as $b$ increases only the positive $\beta$ is permitted. Applying the condition $F_\lambda(0)=1$ then leaves $$ F_\lambda(b)=e^{-\beta b} \text{ where } \beta=\sqrt{\frac{\mu^2}{\sigma^4}+\frac{2\lambda}{\sigma^2}}-\frac{\mu}{\sigma^2}. $$ Note that if we set $\lambda=0$ this give the likelihood that $X_t=b$ is ever reached, which is $1$ if $\mu\ge0$.

share|improve this answer

mejor te escribo en castellano no? Tengo problemas con el ejercicio 2 apartados 1 y 3 del tema 1, así como con el ejercicio 1 del tema 2 y el ejercicio 2 apartado d del tema 2. ¿Podrías ayudarme? Respecto al que me pides, mira este link: http://www.columbia.edu/~hz2244/teaching/Lec9.pdf A ver si hay suerte!!! Saludos

share|improve this answer
    
Thank you VMS. Do you have an email address where I can send you some hints? –  RCA Sep 14 '12 at 8:46
    
If you want, I can provide you more solutions. –  VMS Sep 14 '12 at 10:06
    
Where are you RCA? Please, give me a reply.... –  VMS Sep 14 '12 at 12:21
1  
+1 for the link but -1 for the miscellaneous discussion that doesn't relate to the question. –  Nate Eldredge Sep 23 '12 at 14:18

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.